Personal Hygiene and Microbial Contamination of Mobile Phones of Food Vendors in Ago-Iwoye Town, Ogun State, Nigeria - Ilusanya, O.A.F.; Adesanya, O.O.; Adesemowo, A.; Amushan, N.A. (Pakistan Journal of Nutrition, 2012)
The microbial contamination of mobile phones belonging to food vendors in different canteens in Ago-Iwoye town, Ogun State was investigated. Fifty swab samples were randomly collected from the food vendors. Sterile swabs were firmly pressed on the handset both front and back and then inoculated into nutrient, MacConkey and Sabroud dextrose agar for bacteria and fungi growth. The predominant bacteria isolated were Staphylococcus aureus (50%), Streptococcus faecium (34%) Bacillus cereus (32%), Escherichia coli (26%), Micrococcus luteus (10%), while the fungi isolated were Penicillium notatum (24%), Aspergillus fumigatus (16%), Aspergillus niger (14%), Mucor sp. (14%) and Aspergillus flavus (4%). It was concluded that mobile phones of food vendors pose a potential health threat to consumers. Personal hygienic and sanitation measures such as hand washing, cleaning of the environment and washing of hand before and after handling of food and phone decontamination should be adopted by food vendors to prevent food borne disease.